Aspectos cuantitativos y temáticos de la producción científica del Departamento de Biblioteconomía y Documentación de la Universidad Complutense de Madrid (1984-2003) - López Yepes, José; Salvador Bruna, Javier (Revista General de Información y Documentación, 2007)
Using a methodology based on the cites received by the researchers of the “Biblioteconomía y Documentación” Area of the UCM, a study about main researchers and publications is done, also taking into account the influence of the UCM in other academic and profesional institutions, and the more relevant topics covered. It is a case study previous to the qualitative analysis of the cites, that is described and considered as a valid tool to improve the results of the traditional quantitative method.